RESISTENSI AGAMA DAN BUDAYA MASYARAKAT - David Samiyono (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2013)
Ethnic group, religion, and cultural interactions are familiar phenomena in Bali. Such an interraction had been there since the island became the locus for trading activities. The concept of Tri hita karana is underlying the harmony on the relations of human beings and God (perhyangan), human beings each others (pawongan) and human beings with the environment (palemahan). Bali is changed now. The culture orientation is on services related to tourism. Bali blast on October 2002 and 2005 effected on the on guard among Baliness. Ajeg Bali is a local wisdom of Baliness –religions and cultures— in order to anticipate outside influences effected toward any aspect of life. The problem in this research is weather Ajeg Bali, as local wisdom able to damm outside culture toward Baliness culture, religion, and economics.